La performance énergétique des bâtiments à l’ère des politiques européennes de démonstration. Le cas du programme CONCERTO et du projet de la ZAC De Bonne (Grenoble, France) - Olivier Labussière (VertigO)
This paper proposes to explore the emergence of demonstration practices in the field of energy efficiency buildings, following in this the approach diffused by the european policies of technological innovation. To do so, it looks at the European CONCERTO program and the French project of Caserne De Bonne, the first french eco-district. After a conceptual insight into the works about the demonstration practices (i), this paper gives some context on the Lisbon Strategy and outlines the ambitions of the European CONCERTO (ii), then it pays attention to the project of the eco-district of De Bonne (Grenoble, France) through a multi-scalar analysis (local, national, european) (iii), before opening a discussion on the issue of time into demonstration practices and their contradictory effects in terms of learning and collective dissemination (iv).